DINAMIKA KETERSEDIAAN BERAS : SEBUAH STUDI KASUS DI KALIMANTAN SELATAN - Alan Dwi Wibowo (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The availability of rice have an impact on the stability of the economic, social, and security of a region, further rice as a staple food has a strategic position. Therefore, it needs to be managed properly to ensure their availability in order to maintain the regional stability. This paper aims to investigate the leverage point in rice production model, where the leverage point will serve as the basis for the availability of rice policies model development which will support food security protocols. System dynamics approach is used in this study, while Kalimantan Selatan is selected as case study. As the result, productivity and land management became a major leverage point in order to escalate rice production in Kalimantan Selatan.